Oral health-related quality of life among adult smokeless tobacco users and nontobacco users of Ghaziabad district, Uttar Pradesh: A cross-sectional study - Iram Ahsan; Ipseeta Menon; Ritu Gupta; Vikram Arora; Asifa Ashraf; Dipshikha Das (Wolters Kluwer Medknow Publications, 2021)
Introduction: Smokeless tobacco (ST) being a crucial determinant of oral health and oral health-related quality of life is a part of many religious and cultural rituals which has gained a degree of social acceptance in the Indian subcontinent. Aim: The aim of this study was to assess the oral health-related quality of life (OHRQoL) among adult ST users and nontobacco users of Ghaziabad. Materials and Methods: A hospital-based cross-sectional study was designed to determine the oral health status and OHRQoL of ST users and nontobacco users. A sample of 620 adult individuals was taken. A pretested questionnaire was used to collect the demographic variables. Oral health status was assessed using the World Health Organization 2013 Oral Health Assessment Form, and OHRQoL was measured with the Oral Health Impact Profile-14. Statistical analysis was done by the Statistical Package for the Social Sciences version 20.0. Chi-square test, Spearman's correlation coefficient, Mann-Whitney U-test, and Kruskal-Wallis test were applied. Statistical significance was considered at P < 0.05. Results: In ST users, 90.3% had gingival bleeding, whereas 58.4% of the nontobacco users had gingival bleeding; 53.2% of the ST users had periodontal pocket compared to 47.7% of the nontobacco users. ST users had higher mean scores on the handicap (1.96 ± 1.29), psychological disability (1.89 ± 2.66), psychological discomfort (1.44 ± 1.31), functional limitation (0.92 ± 1.35), physical pain (0.79 ± 0.91), and social disability (0.52 ± 0.70) when compared to the nontobacco users. A ST user has a higher (8.03 ± 4.14) mean score when compared to nontobacco users (4.56 ± 4.01) (P < 0.001) in all subscales of OHRQoL. A statistically significant difference in the oral OHRQoL between ST users and nontobacco users was observed. Conclusion: Hence, the study revealed that ST users definitely had an influence on OHRQoL, with a statistically significant increase in oral health problems in ST users compared to nonusers.